1990
DOI: 10.1111/j.1439-0450.1990.tb01051.x
|View full text |Cite
|
Sign up to set email alerts
|

Some Diagnostic Features of the Pathogenesis of Bovine Paratuberculosis (Johne's Disease) and Serum Biochemical Changes after Oral Reinfection

Abstract: Summary Ten bull‐calves were infected with 108 viable cells of Mycobacterium paratuberculosis per os. During the 400‐day period of observation faecal and blood samples were taken from animals at 30‐day intervals. Faecal samples were examined microscopically, blood samples by the CFT, AGID and LST tests. Intradermal allergic tests were carried out at PI (post infection) days 92, 217, 336, using mammalian, avian and johnin PPD. In the period of study, these efficiency indices showed fluctuations characteristic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
(3 reference statements)
0
7
0
Order By: Relevance
“…In conformity with our results, they did not find differences in BHB, bilirubin and cholesterol levels and ALT activity in MAP-shedding cows. Earlier studies also reported lower levels of TP in subclinically infected calves (Szilágyi et al, 1989;Körmendy et al, 1990). McGregor et al (2015) reported that several biochemical parameters, except serum albumin, were similar between MAP-positive and MAP-negative Merino sheep.…”
Section: Discussionmentioning
confidence: 91%
“…In conformity with our results, they did not find differences in BHB, bilirubin and cholesterol levels and ALT activity in MAP-shedding cows. Earlier studies also reported lower levels of TP in subclinically infected calves (Szilágyi et al, 1989;Körmendy et al, 1990). McGregor et al (2015) reported that several biochemical parameters, except serum albumin, were similar between MAP-positive and MAP-negative Merino sheep.…”
Section: Discussionmentioning
confidence: 91%
“…The results of our study showed in cows with chronic diarrhoea associated with seropositivity to MAP infection lower concentrations of total serum proteins, which was more marked in high MAP-positive animals. Lower total protein concentrations in MAP-positive dairy cows compared with MAP-negative animals were observed also in German Holstein dairy herds and in young bulls with paratuberculosis (Szilágyi et al 1989;Körmendy et al 1990;Donat et al 2014). According to Raizman et al (2007), hypoproteinemia may be found not only in cows with severe clinical signs of paratuberculosis and high shedder animals, but also in moderate or low shedders, although to a lower extent.…”
Section: Discussionmentioning
confidence: 95%
“…The overall biochemical changes indicated a distinct change in the group of biochemicals that were related to the early stages of the infection, while the biochemicals that are related to the muscles and liver functions were mostly increased at the late stages of the infection [32].…”
Section: The Biochemical Changes Of Ptb In Cattlementioning
confidence: 95%
“…The biochemical changes were monitored in calves experimentally infected with MAP [32]. The TRP, ALB, TRIG and CHOL indicated significant decrease by day 400 post infection (PI).…”
Section: The Biochemical Changes Of Ptb In Cattlementioning
confidence: 99%
See 1 more Smart Citation